Sturge-Weber syndrome: Clinico-neuroradiological features and treatment profile - Chatterjee, Anirban; Sinha , Malay Kumar (Nepal Journal of Neuroscience, 2021)
Introduction:  Sturge Weber syndrome (SWS) is a rare, nonhereditary genetic disorder. SWS belongs to a diverse group of Neurocutaneous disorders. A somatic mutation in the early development of cells in SWS patients causes the formation of a congenital capillary vascular malformation. SWS is characterized by nevus flammeus on the face (also called Port-Wine Birthmark), brain (leptomeningeal angioma), and eyes (glaucoma).Methods and Materials: We present three patients diagnosed with Sturge Weber syndrome who attended a teaching hospital between 2013 to 2016. The clinical, neuroradiological features and treatment of SWS patients were reviewed retrospectively from medical records.Results: Two males and females with SWS were reviewed. The facial nevus flammeus was unilateral in one patient and bilateral in two patients. The extensive nevus flammeus including the face, trunk, and upper limb was found in one patient. Epilepsy, neurodevelopmental delay, and intellectual disability were the most common presentation in the series. Episodic hemiparesis was manifested in one patient. Levetiracetam and oxcarbazepine, either single or combined, were used in every SWS patient (n=3). Six months seizure-free was obtained in a patient with SWS with combined anticonvulsant therapy. Conclusion: Drug-refractory and early-age epilepsy is associated with lower intelligence level that consequently affects poor social skill and quality of life in the patients with SWS. Sudden or gradual loss of vision is also a threat for SWS patients. Diagnosis at birth or during early age, multidisciplinary intervention, and follow-up is a must to improve absolute outcomes in the patients with SWS.